HISTORY AND ORIGIN OF SURNAMES - Koziyeva Iqbol Komiljonovna, (World Scientific Research Journal, 2025)
Abstract: The article discusses the morphological structure and semantics of Russian surnames. Russian Russians also consider the specific features of the development of Russian society, the formation of Russian surnames and their spread. The article also talks about the distinctive features of onomastics in Western European countries, where stable local variants can be traced.